1997
DOI: 10.1016/s0735-1097(97)00016-8
|View full text |Cite
|
Sign up to set email alerts
|

Combination of Dobutamine and Myocardial Contrast Echocardiography to Differentiate Postischemic From Infarcted Myocardium

Abstract: Contractile reserve and perfusion data are complementary when assessing regional wall motion abnormalities in postischemic myocardium. DE alone cannot differentiate postischemic from infarcted myocardium; simultaneous data on myocardial perfusion are required. The combination of DE and MCE is superior to either technique alone for identifying the absence of myocardial necrosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
7
0

Year Published

1997
1997
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(9 citation statements)
references
References 51 publications
2
7
0
Order By: Relevance
“…Our findings are in agreement with those of Meza et al, 17 who recently demonstrated in a canine model that the presence of contractile reserve in itself does not exclude the presence of regional necrosis. In their study, dogs with MI documented by TTC staining had significant improvement in regional function (percent thickening fraction went from Ϫ7Ϯ22% after reperfusion to 14Ϯ13% with 10 g ⅐ kg Ϫ1 ⅐ min Ϫ1 dobutamine).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Our findings are in agreement with those of Meza et al, 17 who recently demonstrated in a canine model that the presence of contractile reserve in itself does not exclude the presence of regional necrosis. In their study, dogs with MI documented by TTC staining had significant improvement in regional function (percent thickening fraction went from Ϫ7Ϯ22% after reperfusion to 14Ϯ13% with 10 g ⅐ kg Ϫ1 ⅐ min Ϫ1 dobutamine).…”
Section: Discussionsupporting
confidence: 93%
“…23 With more rapid imaging, more myocardial regions could be sampled, and 2-and 3-dimensional analysis 24,25 of the tagged MR images could be performed, yielding important information with regard to the direction of intramyocardial strains although sacrificing the transmural resolution of the 1-dimensional technique. The combination of quantitative assessment of functional reserve and assessment of myocardial perfusion by either myocardial contrast echocardiography 17,26 or MR contrast imaging may be superior to either technique alone. Our group and others have recently demonstrated the utility of MR contrast infusion to evaluate patients with MI 27,28 and predict return of function on the basis of contrast uptake patterns.…”
Section: Future Directionsmentioning
confidence: 99%
“…28,[31][32][33][34][35][36] The strengths of echocardiography-based techniques include safety, portability, low cost, and widespread availability of equipment. The main limitation is that the technique is highly operator dependent with high interobserver and intercenter variability.…”
Section: Assessment Of Viabilitymentioning
confidence: 99%
“…[1][2][3][4][5][6][7] From MCE produced by direct coronary injection, patterns of opacification consisting of absent, partial/patchy, 3,6 and normal uptake [1][2][3][4][5][6][7] have been observed in the reperfused zone shortly after recanalization. The absence of myocardial opacification after reperfusion has been associated with necrosis, as evidenced by a failure to recover function at follow-up.…”
mentioning
confidence: 99%
“…Of greatest importance, it has been found that myocardial dysfunction may occur even in the presence of contrast enhancement 4 -6 and that an additional assessment of the response to dobutamine stress may be necessary to establish viability. 6,7 Thus, alternative methods by which to identify infarcted but opacified myocardium after reperfusion are needed.…”
mentioning
confidence: 99%